Dicistronic regulation of fluorescent proteins in the budding yeast Saccharomyces cerevisiae - Edwards, Sarah R. (2010)
Fluorescent proteins are convenient tools for measuring protein expression levels in the budding yeast Saccharomyces cerevisiae. Co-expression of proteins from distinct vectors has been seen by fluorescence microscopy; however the expression of two fluorescent proteins on the same vector would allow for monitoring of linked events. We engineered constructs to allow dicistronic expression of red and green fluorescent proteins and found that expression levels of the proteins correlate with their order in the DNA sequence, with the protein encoded by the 5'-gene more highly expressed. To increase expression levels of the second gene we tested four regulatory elements inserted between the two genes: the IRES sequences for the YAP1 and p150 genes, and the promoters for the TEF1 gene from both Saccharomyces cerevisiae and Ashbya gossypii. We generated constructs encoding the truncated ADH1 promoter driving expression of the red protein, yeast-enhanced Cherry, followed by a regulatory element driving expression of the green protein, yeast-enhanced GFP. Three of the four regulatory elements successfully enhanced expression of the second gene in our dicistronic construct. We have developed a method to express two genes simultaneously from one vector. Both genes are codon-optimized to produce high protein levels in yeast, and the protein products can be visualized by microscopy or flow cytometry. With this method of regulation the two genes can be driven in a dicistronic manner, with one protein marking cells harboring the vector and the other protein free to mark any event of interest.